Awareness of and awareness that: their combination and dynamics. - Fernández-Fernández, Claudia; Velázquez Quesada, Fernando Raymundo (Oxford University Press, 2020)
The paper proposes a logical framework representing the notion of explicit knowledge as the combination of awareness of and awareness that. The setting, semantically combining neighbourhood models with ideas from awareness logic, separates the mere fact of entertaining some information (being aware of phi⁠) from the acknowledgement that the information is indeed the case (being aware that phi holds). The text discusses not only the main properties these concepts obtain under the given representation, but also several of the epistemic actions that can be defined, and the way they affect the agent’s awareness (and thus her knowledge).
https://v2.sherpa.ac.uk/id/publication/664
Keywords: Lógica epistémica; Conciencia; Awareness,; Explicit knowledge; Epistemic logic; Awareness logic; Neighbourhood semantics; Epistemic actions; Dynamic epistemic logic